Lysine Demethylase JMJD1B (KDM3B); A Target Enabling Package - Brennan, P (University of Oxford, 2018)
A description of the materials and methods is included within the TEP datasheet. There are 3 members of the Lysine Demethylase JMJD1 (KDM3) family, JMJD1A-C. SGC Oxford has expressed, purified and crystallized the catalytic domains of JMJD1A, JMJD1B and JMJD1C as part of the probe programme. Fragment screening and X-ray crystallography identified a large number of binders, some of which were progressed into a medicinal chemistry programme. Despite significant effort molecules with probe properties were not obtained. Consequently it has been decided to put the information generated into the public domain.